2000
DOI: 10.1152/ajpendo.2000.278.5.e778
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training increases FFA oxidation and reduces triacylglycerol utilization in contracting rat soleus

Abstract: We examined the effects of 8 wk of intense endurance training on free fatty acid (FFA) transporters and metabolism in resting and contracting soleus muscle using pulse-chase procedures. Endurance training increased maximal citrate synthase activity in red muscles (+54 to +91%; P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
50
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 43 publications
11
50
1
Order By: Relevance
“…Recent studies in our laboratory (12,23,24) and others (28,29) have demonstrated that fatty acid transporter expression is regulated by the metabolic demand of skeletal muscle (23), obesity (28,29), and diabetes (29). These latter studies (28,29) suggest that there may be hormonal regulation of fatty acid transporter expression, resulting in altered rates of plasmalemmal fatty acid transport.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies in our laboratory (12,23,24) and others (28,29) have demonstrated that fatty acid transporter expression is regulated by the metabolic demand of skeletal muscle (23), obesity (28,29), and diabetes (29). These latter studies (28,29) suggest that there may be hormonal regulation of fatty acid transporter expression, resulting in altered rates of plasmalemmal fatty acid transport.…”
Section: Discussionmentioning
confidence: 96%
“…To detect FAT/ CD36 and FABPpm, we used antibodies and procedures that have been described previously (12,15,17,23). Messenger RNA for FAT and FABPpm were measured in red and white vastus muscle using procedures previously described (24).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic effects of exercise training (8-12 wk) on skeletal muscles CS activity have been extensively examined in rats (1,6,20) and humans (4,14). In the present study, we have found that soleus muscle from the trained rats 48 h after the last training session had a 25% higher level of CS activity compared with the sedentary rats (T 48 vs. C: 412 Ϯ 10.9 vs. 330 Ϯ 6.6 nmol ⅐ mg protein Ϫ1 ⅐ min Ϫ1 , P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, palmitate incorporation into phospholipids, triacylglycerol, and diacylglycerol was determined by measuring [ 14 C]palmitate accumulation in these depots in selected rat hindlimb muscles (soleus and red and white gastrocnemius) as we have previously reported (10)(11)(12)(13). This permitted us to calculate the incorporation rates of palmitate in the whole rat hindlimb musculature from the known muscle fiber composition of these muscles and the known proportions of their muscle fiber mass in the rat hindlimb (3), as we (20) have done previously when determining glucose transport for the whole hindlimb muscle from selected individual muscles.…”
Section: Methodsmentioning
confidence: 99%